Local anesthetics systemic toxicity in children: analysis of the French pharmacovigilance database - Arnaud Schweitzer-Chaput; Delphine Callot; Naim Bouazza; Fabrice Lesage; Mehdi Oualha; Nathalie Paret; Marie Boyer-Gervoise; Jean-Marc Treluyer; Laurent Chouchana (BMC, 2023)
Abstract Purpose To characterize clinical profile of pediatric local anesthetic (LA) systemic toxicity (LAST) and to identify determinants of life-threatening outcomes. Methods Spontaneous reports notified to the French Pharmacovigilance Network were retrieved and followed by a case-by-case review, according to the following criteria: LA as suspected drug, age < 18 years, adverse drug reactions related to nervous system, cardiac, respiratory, psychiatric or general disorders. Multivariate logistic regression analysis was performed to identify factors leading to life-threatening reaction (i.e. continuous seizures or cardiorespiratory arrest). Results Among 512 cases retrieved, 64 LAST cases were included (neonates 11%, infants 30%, children 36%, adolescents 23%) mainly involving lidocaine (47%), lidocaine + prilocaine (22%) and ropivacaine (14%). Toxicity profiles were neurological (58%), cardiac (11%) or mixed (20%) and 7 patients (11%) developed methemoglobinemia. LAST was life-threatening for 23 patients (36%) and 2 patients died. Doses were above recommendations in 26 patients (41%) and were not different between life-threatening and non-life-threatening cases. The context of use (general and orthopedic surgery, p = 0.006) and the type of LA agent (lidocaine, p = 0.016) were independently associated with a life-threatening outcome. Conclusion In this national retrospective analysis, LAST in children appear to be a rare event. Neurological and cardiac signs were the most frequently reported reactions. LAST in children can be life-threatening, even at therapeutic doses. Although a fatal outcome may anecdotally occur, the vast majority of patients recovered after appropriate medical care.